Hypoxia Imaging of Tumor and Spatiotemporal Analysis during Oxygen Inhalation. Issue 10 (October 2014) - Yamada, Ryo; Horinouchi, Hirohisa; Tsukada, Kosuke
SUMMARY Tumor hypoxia is considered a potential therapeutic problem because it reduces the effects of radiation therapy. Clinical experience has shown that long‐term tumor oxygenation cannot be achieved with oxygen inhalation, but the mechanisms behind this phenomenon remain unknown. In this study, we designed an optical system for evaluating spatiotemporal changes in tissue oxygen tension (pO2) by phosphorescence quenching. The system can measure continuous changes in pO2 at a fixed point and can also perform two‐dimensional mapping of pO2 in any part of the tumor tissue. We implanted tumor tissue in a dorsal skinfold chamber (DSC) of C57BL/6 mice and observed tumor growth. The mice received oxygen inhalation and pO2 was measured. Tumor pO2 increased after inhalation but the oxygen level was not maintained despite continuous inhalation of pure oxygen; the tumor returned to a hypoxic state. These results mimic the clinical experience of oxygen inhalation treatment in radiation therapy. Our system reproduces the repeat hypoxic phenomenon in a murine tumor model and can be used to determine the mechanisms of oxygen metabolism in tumors.